Relevance of the Central Curriculum Topics in Social Education Study Program to the Demands of the Digital Era - Nuryana Nuryana; Yunita Yunita; Euis Puspitasari (ASANKA : Journal of Social Science and Education, 2024)
The 4.0 industrial revolution demands changes in all fields, including education. Every educational institution is required to produce graduates with good digital competencies and be able to observe digital phenomena in their surroundings, help combat cyberbullying, fight hoaxes, and create educational content. This research aims to prove the relevance between the core curriculum topics and the competency demands required in the workplace. This research uses a quantitative approach with a survey method. The survey was conducted on users and alumni of Tadris IPS (Social Studies Education) spread across the regions of Cirebon, Indramayu, Majalengka, and Kuningan. The research results show that: 1) The Tadris IPS Curriculum, which is based on the KKNI (National Higher Education Curriculum Framework) curriculum, is still relevant to be implemented, but it still has weaknesses in accommodating 21st-century skills. 2) The graduate competencies needed in the digital era are graduates who have good digital literacy and are able to collaborate with students regarding the use of digital media and master the security and ethics of using digital media. 3) The relevance of the Tadris IPS curriculum to the demands of the workplace is considered to have high relevance. This is evidenced by the survey results which show an average of 65% of courses in the Tadris IPS department are "very relevant" to the competency demands of the workplace.